Peptidomimetics: modifying peptides in the pursuit of better vaccines. (February 2011) - Croft, Nathan P; Purcell, Anthony W
Peptide vaccines represent a potential strategy for the prevention and treatment of pathogenic diseases, cancers and autoimmune disorders; their low cost, ease of synthesis and inherent safety are all attractive features. However, they have remained largely unsuccessful owing to low immunogenicity, predominantly stemming from reduced bioavailability due to rapid proteolytic degradation in vivo . The field of peptidomimetics, through chemical alteration of epitope structure, attempts to modify peptides to engender improved immunogenicity and stability, with the ultimate aim of rationally designing more efficacious vaccines. This article discusses the strategies employed in this process and recent advances within the field.